Genome-wide mapping of Arabidopsis thaliana origins of DNA replication and their associated epigenetic marks - Costas, C.; Sanchez, M.; Stroud, H.; Yu, Y.; Oliveros, J.C.; Feng, S.; Benguria, A.; Benguria, A.; Zhang, X.; Solano, R.; Jacobsen, S.E.; Gutierrez, C.
Genome integrity requires faithful chromosome duplication. Origins of replication, the genomic sites at which DNA replication initiates, are scattered throughout the genome. Their mapping at a genomic scale in multicellular organisms has been challenging. In this study we profiled origins in Arabidopsis thaliana by high-throughput sequencing of newly synthesized DNA and identified ~1,500 putative origins genome-wide. This was supported by chromatin immunoprecipitation and microarray (ChIP-chip)experiments to identify ORC1- and CDC6-binding sites. We validated origin activity independently by measuring the abundance of nascent DNA strands. The midpoints of most A. thaliana origin regions are preferentially located within the 5_O half of genes, enriched in G+C, histone H2A.Z, H3K4me2, H3K4me3 and H4K5ac, and depleted in H3K4me1 1 and H3K9me2. Our data help clarify the epigenetic specification of DNA replication origins in A. thaliana and have implications for other eukaryotes.